Pengaruh CEO Tenure terhadap Audit Fee - Faridah, Jauharotul; Kalanjati, Devi Sulistyo (Politeknik Ganesha Medan, 2024)
This study examines the effect of CEO tenure on audit fees in two different periods, the first three years and the final year of the CEOs’ service. Those two periods were chosen because the CEOs’ are more likely to show high risk-taking behavior and manage earnings as proof of his ability to manage the company when he is about to start and end his service, and to maintain the chair of Board of Directors after retirement. Hence, the first three years and the final year of the CEOs’ service increase the probability of financial misreporting and thus the audit risk compared to other years, so it affects the determination of audit fees by the auditor. The results by using 1157 samples of data from non-finance and non-mining companies listed on the Indonesia Stock Exchange (IDX) from 2010 to 2019 shows a significant effect between CEO tenure and audit fees. This study initiates research on the topic of CEO tenure and audit fees in Indonesia and expands the literature on CEO tenure and audit fees.